BRONCHIAL ASTHMA IN CHILDREN: DIFFICULTIES IN DIAGNOSIS AND TREATMENT - Bazarova Sabina Zafarovna; Haydarova Haticha Ramizovna (Galaxy International Interdisciplinary Research Journal, 2024)
Bronchial asthma in children is an relevant problem in the world and in Uzbekistan asthma is the most common chronic disease of the lower respiratory tract in childhood. Diagnosis of bronchial asthma in children, especially in children of the first five years of life, often causes difficulties. Experts of the Global Strategy for the Treatment and Prevention of Bronchial Asthma (Global Initiative for Asthma, GINA) attribute difficulties in diagnosis to the widespread occurrence of episodes of wheezing in the chest, mainly at the age of less than 3 years; limited possibility or impossibility of testing lung function. The therapeutic and preventive methods used also have age specificity [1]. In this regard, the main attention of specialists is paid to new methods of diagnosing this pathology and developing an optimal treatment regimen for the disease.